Review of Single Step Techniques for Production of ACNT’s (International Journal of Engineering and Computer Science, 2017)
The perpendicular orientation of carbon nanotubes to a substrate are vertically aligned carbon nanotubes (VACNT), and parallel to the substrate are horizontally aligned CNT’s. Their proper and dense alignment along with outstanding physical and chemical properties enables ACNT to be used to may various fields. The most common single step methods to produced aligned carbon nanotubes (ACNT’s) are Thermal pyrolysis and flame synthesis, and both are relatively simple. This review explore different methods used for ACNT growth, the process parameter determine the morphology ACNT and the application of structured ACNT’s.